2011
DOI: 10.1039/c0dt01798a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, structural, computational and (spectro)electrochemical studies of icosahedral carboranes bearing fluorinated aryl groups

Abstract: The icosahedral carboranes 1-C(6)F(5)-2-Ph-1,2-closo-C(2)B(10)H(10) (1), 1-(4'-F(3)CC(6)H(4))-2-Ph-1,2-closo-C(2)B(10)H(10) (2), 1,2-(4'-F(3)CC(6)H(4))(2)-1,2-closo-C(2)B(10)H(10) (3), 1-(4'-H(3)CC(6)F(4))-2-Ph-1,2-closo-C(2)B(10)H(10) (4), 1-(4'-F(3)CC(6)F(4))-2-Ph-1,2-closo-C(2)B(10)H(10) (5), 1,2-(4'-F(3)CC(6)F(4))(2)-1,2-closo-C(2)B(10)H(10) (6), 1,7-(4'-F(3)CC(6)F(4))(2)-1,7-closo-C(2)B(10)H(10) (7) and 1,12-(4'-F(3)CC(6)F(4))(2)-1,12-closo-C(2)B(10)H(10) (8), with fluorinated aryl substituents on cage ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…These ICT states are notable for their flexible carboranyl C−C bond, which can vibrate and relax non‐radiatively, or radiatively with a highly red‐shifted emission 24, 25, 26, 27, 28, 29, 30. Such systems often exhibit aggregation‐induced emission (AIE),13, 14, 15, 17, 18, 19, 20, 22, 31, 32 that is, in an aggregated state where molecular motion is restricted, non‐radiative relaxation pathways from the ICT state are inhibited, leading to a significant increase in emission efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These ICT states are notable for their flexible carboranyl C−C bond, which can vibrate and relax non‐radiatively, or radiatively with a highly red‐shifted emission 24, 25, 26, 27, 28, 29, 30. Such systems often exhibit aggregation‐induced emission (AIE),13, 14, 15, 17, 18, 19, 20, 22, 31, 32 that is, in an aggregated state where molecular motion is restricted, non‐radiative relaxation pathways from the ICT state are inhibited, leading to a significant increase in emission efficiency.…”
mentioning
confidence: 99%
“…When di‐substituted with two naphthyl donor groups, the imposed proximity of the aryl systems allows for an overlap of the aromatic wavefunctions, such that dimerization occurs readily when one naphthalene is in the excited state 27. In other cases where o ‐carborane has been attached to pyrene, the bulky carborane moiety was found not to inhibit the π–π stacking required for pyrene excimer formation 19, 20, 23.…”
mentioning
confidence: 99%
“…With regard to the many closo-and nido-carboranes, carborane-based radical anions featuring a 2n+3 electron count are somewhat rare. [8][9][10][11][12][13] In a more recent report on the photophysics of ortho-carboranes with donating arylcarbazolyl substituents it was suggested that the species in their excited states consist of carbazolyl radical cations and radical cluster anions. This assumption was based on absorption spectroscopy where a transient band at 415 nm with a similar spectral profile as the corresponding radical anion was observed 13 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…When di-substituted with two naphthyl donor groups,t he imposed proximity of the aryl systems allows for an overlap of the aromatic wavefunctions, such that dimerization occurs readily when one naphthalene is in the excited state. [27] In other cases where o-carborane has been attached to pyrene,t he bulky carborane moiety was found not to inhibit the p-p stacking required for pyrene excimer formation. [19,20,23] In these few cases,h owever, the carborane can be considered essentially electronically isolated from the aromatic excimer species,s ave for some electron-withdrawing inductive effects.…”
mentioning
confidence: 99%
“…Ak ey property of o-carborane is its ability to accept an excited charge via intramolecular charge transfer (ICT) from an aryl donor group,o ccurring most efficiently when the carborane has its C À Cb ond perpendicular to the aromatic plane.T hese ICT states are notable for their flexible carboranyl CÀCb ond, which can vibrate and relax nonradiatively,o rr adiatively with ah ighly red-shifted emission. [24][25][26][27][28][29][30] Such systems often exhibit aggregation-induced emission (AIE), [13-15,17-20, 22, 31, 32] that is,i na na ggregated state where molecular motion is restricted, non-radiative relaxation pathways from the ICT state are inhibited, leading to as ignificant increase in emission efficiency. It has been demonstrated that incorporation of bulky carboranes on the long edges of linear acenes creates al arge steric hinderance between the carboranes and proximal protons,l eading to aconsiderable deformation of the ring system.…”
mentioning
confidence: 99%